MORPHOFUNCTIONAL CHANGES OF THE SMALL INTESTINE IN ASCARIASIS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Ascariasis, caused by the parasitization of the nematode Ascaris lumbricoides, is a widespread helminthiasis significantly affecting the morphofunctional state of the small intestine. This article examines the key morphological and functional changes in the small intestine associated with this disease, including inflammatory processes, structural damage to the mucosa, impaired barrier function, and altered digestion and absorption processes. The analysis aims to enhance understanding of the disease's pathogenesis and explore potential approaches to treatment and prevention.